Family Socioeconomic Status, Parents' Level of Education, and Parental Engagement in Educational Activities in Sheema District - Uganda - Mugumya, Duncans; Karooro, Emmanuel; Mwesigye, Adrian Rwekaza (American Journal of Education and Practice, 2023)
Purpose: The purpose of this study was to examine the differences in the levels of parental engagement in the academic activities of learners in government grant-aided secondary schools in Sheema District based on demographic characteristics. Methodology: The study was quantitative in nature and employed cross-sectional survey design. Participants of the study included Senior 4 students as well as their parents and teachers selected using probability. Findings: The results indicated a statistically significant difference among parents of different socioeconomic statuses in engagement in provision of basic needs (X2(4) = 30.994, p < .05), academic communication (X2(4) = 29.317, p < .05), academic decision making (X2(4) = 18.906, p = .001), infrastructure development and maintenance (X2(4) = 11.412, p = .022), provision of a conducive learning environment at home (X2(4) = 25.291, p < .05), and provision of adequate learning resources at home (X2(4) = 41.890, p < .05). Differences in parental engagement were statistically significant among parents of different educational levels in provision of learning materials (X2(4) = 27.901, p < .05). There was no statistically significant difference in parental engagement among parents with 1"”2, 3"”4, and 5 and above school-going dependents. Based on these results, It is argued that family socioeconomic status and level of education influence parents' engagement in their children's learning and subsequent academic success. Recommendation: Government and other key stakeholders to develop and implement policies that can increase parents' socioeconomic status as well as educational attainment in order to engage more fully in the education of their children.